Peran Kepribadian Introvert dan Tekanan Sosial Terhadap Penggunaan Kencan Online - Sadida, Aghnia Hasya; Ratnasari , Yudiana (Riviera Publishing, 2025)
This study aims to examine the role of introverted personality traits and social pressure on the use of online dating applications among young adults. The growing popularity of online dating platforms indicates that both psychological and social factors significantly influence individuals’ decisions to engage in digital relationships. Using a quantitative approach with a survey method, the study involved 107 young adult participants selected through accidental sampling. Instruments included adapted versions of the Big Five Inventory (BFI), Social Pressure Scale, and an online dating usage scale. The findings reveal that introversion has a positive and significant effect on online dating usage, as introverted individuals prefer controlled, text-based interactions. Social pressure also demonstrated a significant impact, indicating that social norms, family expectations, and peer influence contribute to online dating adoption. Furthermore, regression analysis shows that introversion and social pressure jointly contribute meaningfully to online dating behavior. These results highlight that online dating use is shaped by the interaction of internal and external factors and offer practical implications for designing more psychologically accommodating dating application features.